Membangun Pendidikan Tanpa Kekerasan Melalui Internalisasi PAI dan Budaya Religius - Aang Kunaepi (EL-TARBAWI, 2011)
Violence in the world of education becomes a fairly complex and complicated problem. The violence that is practiced is the impact of structural inequality in education system as a whole. Violence can be found in social values, cultural, and structural society factor. Violence in education could be prevented by minimizing the root problem. Violence behavior in education that are not immediately resolved, will generate further violence. To prevent such violence, role of religion, culture, and human values need to be internalized in everyone through Islamic education and religious culture. Education constitutes educational process that empowers people to be able to resolve the conflict with creative ways, and it is not handled by violence. Internalization of education of Islamic religion and culture of religiousity can prevent violence behavior because religion teaches the importance of affections, forgiveness, mutual helping, prioritizing peace than violence, respecting the rights of others, and not insulting, stealing, or even killing each other. In short, internalizing education of Islamic religion and culture can be effectively omit violence because it teaches students peace education, affections and humanity. Therefore it can be used as an alternative solution to discontinue the violent behavior in education.